Development of Independent Value in Elementry Islamic School Mutiara Cendekia - Diharja, Umar; Widiwinarni, Endang; Sasongko, Rambat Nur; Danim, Sudarwan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The value of character education organizes a learning system that encourages the actualization of competence and independence of elementary school students. So that the lesson has become a habit for the local community, especially for elementary school students on the banks of the river who use independent transportation to school. Independence in the development of character education occurs through a value which is a term that cannot be separated from education. This study used a qualitative method, which is a scientific research method that aims to understand a phenomenon in its natural social context by prioritizing a deep communication process between researchers and the phenomenon being studied. The research's findings suggest possible outcomes that can be put into practice to building independent character. For students to successfully develop their own character, it is important for the school, teachers, and parents to work together. The role of the teacher in character development is very important, because the figure of a teacher becomes a source of inspiration and motivation for students. The attitude and behaviour of a teacher is also very imprinted on the students, where every utterance, the personality of a teacher can be a reflection for students. Teachers are not only academic educators but also must be able to become character, moral and cultural educators for their students. The method that is often used in character development is habituation, where teachers can familiarize students to apply certain values based on agreements that have been made together with students, for example about tidiness and this is carried out continuously so that it can become a daily activity, students as well as the teacher.